A memorable visit of STIKes Muhammadiyah Ciamis at UiTM / Fazleen Haslinda Mohd Hatta - Mohd Hatta, Fazleen Haslinda (Faculty of Pharmacy, 2024)
On October 7, 2024, Faculty of Pharmacy, Universiti Teknologi MARA (UiTM) had the pleasure of hosting a distinguished delegation Sekolah Tinggi Ilmu Kesehatan (STIKes) Muhammadiyah Ciamis, Indonesia. This visit was a significant milestone aimed at fostering academic initiatives and research collaborations between the institutions.